Strategi Para Tokoh Agama Dalam Mendidik Kerukunan Eksternal dan Implikasinya terhadap Keutuhan NKRI di Bangka Belitung - Suparta, Suparta (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
There are three strategies carried out by religious leaders in educating religious harmony in their people, especially those related to external harmony.First, the strategy of educating people in the internal harmony of religious people. In this case all religious leaders each agreed to foster their people to live in harmony and peace. Of course this direction is in accordance with the teachings of the respective books. Second, the strategy of educating their people to get along with other fellow religions. They try their best so that every people always respect and respect other religions, they cannot force the will of their religion, they must not mutilate each other and also not harm other religious people. This is also stated in the scriptures in each religion. Third, the strategy of educating the people to get along well with the government. all religious teachings order that they always have good relations and respect for their government. This is because all realize that we live in the same country, namely the Indonesian state in one power and government. So respecting, respecting and fulfilling government rules is a must. The strategy to maintain the integrity of the NKRI was also agreed upon by all religious leaders. They agreed that if the basis of the Indonesian state is Pancasila, don’t change it again. This is because so far what can unite all religious teachings in Indonesia is Pancasila. For this reason the NKRI is intact and will remain intact if all religions maintain the Pancasila.